Dilemma Tales as African Knowledge Practice: An Example From Research on Obligations of Support - Esiaka, Darlingtina; Adams, Glenn; Osei-tutu, Annabella (Frontiers in Psychology, 2020)
This contribution to the Frontiers research topic collection on African Cultural Models considers dilemma tales: an African knowledge practice in which narrators present listeners with a difficult choice that usually has ethical or moral implications. We adapted the dilemma tale format to create research tasks. We then used these research tasks to investigate conceptions of care, support, and relationality among participants in Ghanaian, African American, and European American settings that vary in affordances for embedded interdependence vs. modern individualism. Results revealed hypothesized patterns, such that judgments about the inappropriateness of institutionalized eldercare (vs. home elder care) and prioritization of material support to parent (over spouse) were greater among Ghanaian participants than European American participants. Responses of African American participants were more ambiguous, resembling European American acceptance of institutionalized eldercare relative to Ghanaian participants, but resembling Ghanaian tendencies to prioritize support to parent (over spouse) relative to European American participants. Results illuminate that standard patterns of hegemonic psychological science (e.g., tendencies to prioritize obligations to spouse over mother) are the particular product of WEIRD cultural ecologies rather than context-general characteristics.